The Application of Biodiesel as an Environmental Friendly Drilling Fluid to Drill Oil and Gas Wells - Abdul Razak Ismail (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
The oil and gas industries need to use oil based drilling fluids to drill troublesome rock layers such as sensitive shale formation or to drill very deep oil and gas wells. However, using oil based drilling fluids will create pollution and therefore, environmental regulations on discharge of such drilling fluids have become more stringent because it will give tremendous impacts on the marine life and ecosystem. This research is conducted to formulate a new environmental friendly drilling fluids using vegetable oils derived biodiesel to replace the oil based drilling fluids without reducing their performances. This study focuses on physical properties and biodegradation rate of biodiesel based drilling fluids with respect to its toxicity and compare with the conventional oil based drilling fluids. Several biodiesels which derived from vegetables oils such as palm oil, corn oil and rice bran oil have been used as base oil in formulating ester based drilling fluids. Acute toxicity test and biodegradation test using closed bottle method were tested using local fishes. The result showed that almost all vegetable oils achieve the required physical properties. However, rice bran oil is almost non-toxic since their 50% lethal concentration (LC50) value is felt in the range of 10,000 to 100,000ppm. Besides, rice bran oil is found to be easily degraded as it showed about 80% of biodegradation rate within 28 days. Therefore, rice bran oil drilling fluid offer the best solution in solving the environmental standards compared to other vegetables oils.